Epidemiological pattern of retinoblastoma at the Philippine General Hospital - Romeo B. Espiritu, MD; Arnel A. de Jesus, MD; Eric G. Valera, MD; Gary V. Mercado, MD (Philippine Journal of Ophthalmology)
Objective: To evaluate the epidemiological and clinical patterns of retinoblastoma in a tertiary government hospital.